Optimal treatment of ceftazidime-avibactam and aztreonam-avibactam against bloodstream infections or lower respiratory tract infections caused by extensively drug-resistant or pan drug-resistant (XDR/PDR) Pseudomonas aeruginosa - Kang, Yixin; Xie, Lu; Yang, Jiyong; Cui, Junchang (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Objective: To evaluate the efficacy of ceftazidime-avibactam (CZA) and aztreonam-avibactam (AZA) against bloodstream infections (BSIs) or lower respiratory tract infections (LRTIs) - causing extensively drug-resistance or pan drug-resistance (XDR/PDR) Pseudomonas aeruginosa. Method: The two-fold dilution method was used to determine the minimum inhibitory concentrations (MICs) of CZA/AZA against XDR/PDR P. aeruginosa. Whole-genome sequencing was used to analyze the resistant determinants of each isolate. Monte Carlo simulations (MCSs) were used to evaluate the probability of target attainment (PTA) and the cumulative fraction of response (CFR) of each CZA/AZA dosing regimen via traditional infusion (TI)/optimized two-step-administration therapy (OTAT). Results: P. aeruginosa isolates producing IMP-45, VIM-1, or VIM-2 were inhibited by AZA at a concentration of 2 to 8 mg/ L. All isolates which produced IND-6 plus other serine β-lactamases exhibited high-level resistance to CZA/AZA (MICs ≥64 mg/L). All simulated dosing regimens of CZA /AZA against BSIs-causing XDR/PDR P. aeruginosa achieved a PTA of 100% when the MIC was ≤32 mg/L. Conclusion: AZA was considered as an option for the treatment of infections caused by XDR/PDR P. aeruginosa producing IMP-45, VIM-1, or VIM-2. OTAT with sufficient pharmacodynamic exposures may be an optimal treatment option for XDR/PDR P. aeruginosa with a high-level MIC of CZA/AZA.